FC 131: Kidney Injury Molecule-1-Mediated Small Extracellular Vesicles Uptake is Crucial for Renal Tubulointerstitial Inflammation. (3rd May 2022) - Chen, Jun; Tang, Tao-Tao; LI, Zuolin; Wang, Cui; Shen, Anran; Liu, Bicheng; LV, Linli
Abstract: BACKGROUND AND AIMS: Tubular epithelial cells (TECs) exposed to hypoxia during kidney injury communicate with interstitial inflammatory cells and contribute to tubulointerstitial inflammation. However, whether injured TECs communicate under hypoxia in an autocrine or paracrine manner and contribute to tubulointerstitial inflammation has yet to be identified moieties. The purpose of this study is to explore the role of small extracellular vesicles(sEVs) secreted by hypoxic TECs in the development of renal tubulointerstitial inflammation and the mechanism of sEV-mediated TEC communication. METHOD: Ischemia reperfusion induced kidney injury (IRI) models were established to explore the conditions of hypoxia induced Inflammation as well as tubular kidney injury molecule-1(KIM-1) expression and sEV production. In vitro, hypoxic TEC-derived sEVs (Hypo-sEVs) were applied to culture TECs to explore sEV-mediated tubule communication. Besides, inflammatory cytokine generation was analyzed in hypoxic TECs with silence of KIM-1 and Rab27a. To investigate the mechanism of sEV internalization, uptake efficiency of the recipient TECs was evaluated in conditions of KIM-1 overexpression. Phosphatidylserine (PS) on the surface of Hypo-sEVs was further assayed by nanoflow cytometry (NanoFCM). sEVs isolated from hypoxic TECs with or without labeling were transferred to IRI mice to detect its localization and the consequences on tubulointerstitial inflammation. RESULTS: In IRI mice, hypoxia induced tubule injury as evidenced by tubule HIF-1α and KIM-1 expression as well as tubulointerstitial inflammation were observed. Impressively, we noticed the colocalization of sEV marker (CD63) with KIM-1, which suggested increased sEV production in injured tubules or uptake of sEVs by damaged tubules through KIM-1. Intriguingly, KIM-1 expression also correlated with CD3 + and CD68 + inflammatory cells infiltration. In vitro, stable HIF-1α and KIM-1 expression was detected in hypoxic TECs with significant inflammatory cytokine expression. Notably, increased sEV release was noticed in hypoxic TECs, while hypoxia induced inflammation could be ameliorated when KIM-1 and Rab27a were silenced. Importantly, the inflammatory response of hypoxic TECs induced by exogenous Hypo-sEVs could be partly relieved when KIM-1 was knock down by siRNA transfection. Besides, PS could readily be detected in Hypo-sEVs by NanoFCM suggesting that sEVs may accelerate TEC inflammation via recognizing PS by KIM-1. Correspondingly, Hypo-sEVs localized to tubules with KIM-1 expression and amplified tubulointerstitial inflammation in IRI mice. CONCLUSION: Our studies demonstrate that KIM-1 expressed by injured tubules mediates sEVs uptake via recognizing PS, which participates in TEC communication and augment of tubulointerstitial inflammation induced by hypoxia.